Aplikasi Pengukuran Tingkat Kecemasan Berdasarkan Skala Hars Berbasis Android - Giatika Chrisnawati; Tutuk Aldino (JURNAL TEKNIK KOMPUTER, 2019)
Abstract  - The development of technology that getting increasingly has an impact on a mobile device. In this era, mobile phone is a communication tool that is flexible, easy to carry anywhere, and its function is almost the same as the computer. The operating system that mobile phone has got increasingly. One of them is that Android operating system has grown rapidly and almost dominates the mobile market. The development of technology and the increase of necessities life make people have to work harder to sufficient their life. People compete to sufficient the needs and keep up the development that exists, but not everyone is able to sufficient it. It makes people want to do crimes like theft, corruption, murder, etc. This happens because someone is too obsessed with their desire. so they are afraid and anxious if they cannot sufficient and achieve their desire. Anxiety can be interpreted as an uncertain fear with a feeling of uncertainty and helplessness that can cause an uncomfortable feeling. So, it triggers their self to do bad things. In this phenomenon is needed an application that can be used to determine the level of anxiety because knowing the level of anxiety early can prevent people to do bad things. The measurement applications of anxiety levels with HARS scale are made based on the Hamilton Anxiety Rating Scale (HARS).